Characterisation of the heterogeneity of ovine deleted variant αS1-casein E by a proteomic approach. (February 2019) - Garro, Giuseppina; Caira, Simonetta; Lilla, Sergio; Mauriello, Rosalba; Chianese, Lina
Abstract: The micro-heterogeneity of the ovine αS1 -casein (αS1 -CN) E variant, occurring in Leccese ewe milk, was characterised using a bottom-up, shotgun proteomic approach using two-dimensional gel electrophoresis and reversed phase-high performance liquid chromatography as separation techniques and polyclonal antibodies against αS1 -CN and nano-liquid chromatography-electrospray ionisation-time-of-flight tandem mass spectrometry as identification methodology. Comparing results with the most common genetic variant αS1 -CN C, αS1 -CN E variant showed a reduced number of phosphorylated serine residues (αS1 -CN E -4P versus αS1 -CN C -9P) and a lower measured molecular mass (22241.7 Da versus 23481.5 Da). These differences were due to the αS1 -CN (70–77) amino acid sequence deletion, coded by exon 10, thus triggering the phosphate loss on serine residues located at positions 64, 66, 68 and 75. The loss of four phosphate groups, associated with the lower content of αS1 -CN E, could be negatively related both to cheese-making aptitude of milk and mineral carrier activity.